2021
DOI: 10.1021/acs.jafc.1c03534
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Regular Emission Mechanism of Volatile β-Ocimene with Anti-insect Function from Tea Plants (Camellia sinensis) Exposed to Herbivore Attack

Abstract: Herbivore-induced plant volatiles (HIPVs) play an important role in insect resistance. As a common HIPV in tea plants (Camellia sinensis), β-ocimene has shown anti-insect function in other plants. However, whether β-ocimene in tea plants also provides insect resistance, and its mechanism of synthesis and emission are unknown. In this study, β-ocimene was confirmed to interfere with tea geometrid growth via signaling. Light was identified as the key factor controlling regular emission of β-ocimene induced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The mated wasps need to locate hosts and lay eggs, so the odour cues are extremely important. It was demonstrated that tea plants emitted β-ocimene upon mechanical damage or herbivore feeding (Chen et al, 2021;Jian et al,…”
Section: Discussionmentioning
confidence: 99%
“…The mated wasps need to locate hosts and lay eggs, so the odour cues are extremely important. It was demonstrated that tea plants emitted β-ocimene upon mechanical damage or herbivore feeding (Chen et al, 2021;Jian et al,…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the anti-insect function of some volatiles might be achieved through the upstream signal molecule JA [ 66 ]. It is also proven that β-ocimene released from tea ( Camellia sinensis ) leaves does not affect tea geometrid ( Ectropis grisescens Warren) directly but may change the phytohormone synthesis by fumigating with tea leaves [ 67 ]. Although we have demonstrated that β-ocimene synthesized by GmOCS has an anti-insect function in both soybean and tobacco ( Figure 5 and Figure 6 ), its accurate anti-insect mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…( E )-β-ocimene in flower and leaves of pear has multiple ecological roles in attracting pollinators and plant-pest interactions ( Scutareanu et al., 2003 ; Su et al., 2022 ). The TPS in catalyzing ( E )-β-ocimene biosynthesis, namely ( E )-β-ocimene synthase, has been functionally characterized in several plant species such as Antirrhinum majus ( Dudareva et al., 2003 ), Arabidopsis thaliana ( Fäldt et al., 2003 ), Camellia sinensis ( Chen et al., 2021 ; Jian et al, 2021 ), Citrus unshiu ( Shimada et al., 2005 ), Lotus japonicus ( Arimura et al., 2004 ), Malus domestica ( Nieuwenhuizen et al., 2013 ), Matricaria recutita ( Irmisch et al., 2012 ), Medicago truncatula ( Navia-Giné et al., 2009 ), Morus notabilis ( Ding et al., 2020 ), Nicotiana attenuata ( Xu et al., 2020 ), Osmanthus fragrans ( Zeng et al., 2015 ), Phaseolus lunatus ( Arimura et al., 2008 ), Populus trichocarpa ( Irmisch et al., 2014 ) and Vitis vinifera ( Martin et al., 2010 ). In the current study, the ( E )-β-ocimene synthase gene PbeOCS was present in the RNA-seq data and functionally characterized in vitro ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%